Brochure on Public Sector Undertakings in Andhra Pradesh - Planning Commission (Planning Commission, 1959)
This Brochure on the working of the Public Sector Undertakings in Andhra Pradesh, is the first of the series to be published by the Bureau. Questions are very often asked by members of Legislature and Public in general about the functioning and the financial position of the public undertakings in the State. A Brochure of this nature will go a long way in meeting a long felt need for a publication in this regard. This Brochure has been compiled on the lines of the Brochures brought out by the Central Statistical Organisation on the public undertakings of Government of India. It covers undertakings in which, the Government of Andhra Pradesh have varying degrees of interest, control and responsibility through their representatives in the undertakings in-charge of their direction and management.
Bureau of Economics and Statistics, Andhra Pradesh